2013
DOI: 10.1016/j.cub.2013.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Numb Localizes at Endosomes and Controls the Endosomal Sorting of Notch after Asymmetric Division in Drosophila

Abstract: Numb acts as a cell-fate determinant during asymmetric and stem cell divisions in both vertebrates and invertebrates [1, 2]. In Drosophila, Numb is unequally segregated in asymmetrically dividing sensory organ precursor cells (SOPs). Numb is inherited by the pIIb cell (Notch OFF) and is absent from the pIIa cell (Notch ON) [3, 4]. Numb is required to establish directional Notch signaling during cytokinesis [3, 5-7]. Using real-time imaging of a functional GFP-tagged Numb, we show that Numb relocalizes during c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
125
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(133 citation statements)
references
References 30 publications
8
125
0
Order By: Relevance
“…30 Numb is a cell-fate determinant that is localized to endosomes, controlling cell-fate choices by asymmetrically partitioning at mitosis and antagonizing Notch family plasma membrane receptor activity. [32][33][34] According to our results, Notch receptors Notch-2, -3, -4, and Notch ligand Jagged-1, -2, Deltal-3, as well as RBP-Jκ mRNA and protein expression significantly increased after BDL. So, Notch signaling enhanced bile duct proliferation.…”
Section: Discussionmentioning
confidence: 81%
“…30 Numb is a cell-fate determinant that is localized to endosomes, controlling cell-fate choices by asymmetrically partitioning at mitosis and antagonizing Notch family plasma membrane receptor activity. [32][33][34] According to our results, Notch receptors Notch-2, -3, -4, and Notch ligand Jagged-1, -2, Deltal-3, as well as RBP-Jκ mRNA and protein expression significantly increased after BDL. So, Notch signaling enhanced bile duct proliferation.…”
Section: Discussionmentioning
confidence: 81%
“…5 These observations indicated that Numb regulates the endosomal trafficking of Notch during cytokinesis, and suggested that Numb breaks the symmetry of Notch distribution along the cytokinetic furrow between pIIa and pIIb, hence leading to directional signaling and binary fate decision.…”
Section: Inhibition Of Notch Recycling By Numbmentioning
confidence: 95%
“…4,6 Live imaging analysis of a functional Sanpodo-GFP protein combined with antibody uptake assays revealed that Notch and Sanpodo are co-internalized during cytokinesis, suggesting that Notch is endocytosed as Notch-Sanpodo oligomers. 4,5 Since Numb regulates the endosomal accumulation of Notch and Sanpodo in pIIb endosomes, it is likely that Numb somehow regulates the accumulation of Notch in sorting endosomes through its interaction with Sanpodo. Since Numb physically interacts with the AP-2 complex, one possibility would be that Numb regulates the AP-2-dependent internalization of Notch-Sanpodo oligomers.…”
Section: Inhibition Of Notch Recycling By Numbmentioning
confidence: 99%
See 1 more Smart Citation
“…Notch is constantly endocytosed (McGill et al, 2009), and the signaling outcome arising from this internalized pool of Notch is carefully controlled by several factors. On the one hand, the protein Numb is a conserved inhibitor of the pathway that acts at this level (Cotton et al, 2013;Couturier et al, 2013Couturier et al, , 2014Reichardt and Knoblich, 2013). This factor interacts with components of the AP-2 complex and prevents endosome-to-plasma membrane recycling of Notch; in addition, Numb also promotes the lysosomal degradation of the receptor (McGill et al, 2009).…”
Section: Discussionmentioning
confidence: 99%